2002
DOI: 10.1016/s0014-5793(01)03322-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial RNase P by aminoglycoside–arginine conjugates

Abstract: The potential of RNAs and RNA^protein (RNP) complexes as drug targets is currently being explored in various investigations. For example, a hexa-arginine derivative of neomycin (NeoR) and a tri-arginine derivative of gentamicin (R3G) were recently shown to disrupt essential RNP interactions between the trans-activator protein (Tat) and the Tat-responsive RNA (trans-activating region) in the human immunodeficiency virus (HIV) and also inhibit HIV replication in cell culture. Based on certain structural similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Recently several such inhibitors have been developed that work at low concentrations [38]. Therefore, protein synthesis inhibitors and RNase P inhibitors may also have a synergistic e¡ect on promoting pathogenic bacterial inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Recently several such inhibitors have been developed that work at low concentrations [38]. Therefore, protein synthesis inhibitors and RNase P inhibitors may also have a synergistic e¡ect on promoting pathogenic bacterial inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…EMSA demonstrating the ability of NeoR to trap 80S complexes on an mRNA template+ Ribosome binding assays were performed in wheat germ extracts with 32 P-labeled mRNA (50,000 cpm/reaction) in the presence of GMP-PNP (lane 1), cycloheximide (Chx; lane 2), cycloheximide and NeoR (lane 3), and 10 mM NeoR (lane 4)+ Complexes were resolved by polyacrylamide gel electrophoresis on native gels using conditions previously described (Lorsch & Herschlag, 1999)+ Following electrophoresis, the gel was dried and exposed to X-OMAT X-ray film (Kodak) at Ϫ70 8C with an intensifying screen+ The positions of migration of the 48S and 80S complexes are indicated by arrows, as is the position of the wells of the gel+ The asterisk indicates a complex whose identity is not known (possibly a 40S ϩ 80S complex) and that may correspond to the complexes present in the shoulder observed at fraction #15 of Figure 6A+ 1276 M. Carriere et al Aminoglycosides interact in complex ways with the prokaryotic ribosome+ They interfere with A-site function and some stimulate misreading of the mRNA template, resulting in the incorporation of the wrong amino acid + Neomycin and hygromycin have also been reported to block translocation (Hausner et al+, 1988) and more recently, neomycin and paromomycin have been shown to inhibit 30S ribosomal subunit assembly (Mehta & Champney, 2002)+ Given the steric bulk of AACs, as well as the presence of multiple arginine functional groups (compared to aminoglycosides), we suspect that AACs interact with a different site on the ribosome+ Our studies have not addressed the nature or location of the AAC binding site, but they could bind to either or both ribosomal subunits+ Binding to the 40S subunit could be feasible if induced structural changes altered activity of the peptidyl transferase site of the 60S subunit+ It will be interesting to test these possibilities in future experiments+ Additional properties of AACs include inhibition of Tat/ Tar interaction (Litovchick et al+, 2000), downregulation of the chemokine CXC receptor type 4 (Litovchick et al+, 2001), and inhibition of bacterial RNase P (Eubank et al+, 2002), suggesting that AACs (especially NeoR) could be considered for both HIV and bacterial chemotherapy+ In this report, we now demonstrate that AACs can inhibit eukaryotic translation+ We do not know if these activities of AACs are intimately linked or can be separated into different activities of the AACs+ Clearly, in-depth structure-activity relationship studies could help assign the different properties to functional groups+…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, aminoglycoside antibiotics bind the major groove of the 16S rRNA to disrupt the fidelity of tRNA selection and block protein translation, but recent studies have revealed that they can also bind and affect the function of mRNAs, tRNAs, and catalytic RNAs (41,(48)(49)(50). Indeed, neomycin B and/or derivatives have been shown to bind to the rnpB component of RNase P and/or precursor tRNA molecules in a manner that inhibits Escherichia coli, Neisseria gonorrhoeae, Porphyromonas gingivalis, Streptococcus pneumoniae, and Bacillus subtilis RNase P function (41,51,52). Accordingly, we evaluated whether neomycin also inhibits S. aureus RNase P activity using an ).…”
Section: Agents That Potentiate the Antimicrobial Activity Of Mupirocinmentioning
confidence: 99%